Prinsip 3Rs dan Pedoman ARRIVE pada Studi Hewan Coba - Salva Reverentia Yurista; Rafi Andika Ferdian; Djanggan Sargowo (Jurnal Kardiologi Indonesia, 2016)
The use of animals in research has concerned the general public and thoughtful researchers for a long time. For improved animal welfare and increased research quality, researchers have moral obligations to include the 3Rs. The Three Rs are basic principles of humane experimental technique that were first set out by Russell and Burch in 1959. They are now widely accepted within the international scientific community and in associated legislation and guidelines, as a means of avoiding or reducing animal use and suffering and helping to improve the quality of science. When reporting animal studies, it is recommended that manuscripts conform to the principals of the Animals in Research: Reporting In Vivo Experiments (ARRIVE) guidelines, incorporated the 3Rs principal.